Integrated platform for Agriculture in India using ICT platform mGAP :Survey - *, Ayonija; Singh, Deepak (IJRDO -Journal of Computer Science Engineering, 2016)
This project is going to develop to improve quality of food material and farmer growth. This platform will provide better product through farm by using best practices and Agro-Expert advisory system to Farmer through mGAP® . So this best agriculture practice and AgroExpert suggestion will help the farmer to develop better quality of product and will standalone at global market.